Cultural values: A conduit of shaping managerial thinking in Zimbabwe’s industrial relations - Farai Ncube (Academic Journals, 2023)
Knowledge production remains a game of power. Over the years certain discourses have tried to naturalise and reinforce the position that world’s best practices are defined as Eurocentric and henceforth anything that is African is viewed as ‘traditional’ , ‘barbaric’ and ‘bush’. The European ‘supremacy’ in knowledge production has been emphasised across disciplines and human resource (HR) management is no exception. It has been argued that ‘true’ human resource management policies were ‘invented’ by Europeans. This has however, fanned discord in industrial relations in Zimbabwean organisations. Employing a theoretical and literature review approach, this research critically explores the extent to which harmony and productivity can be achieved in Zimbabwe if managers adopt the ‘true’ Zimbabwean cultural values and allow them to shape their managerial thinking. This study contends that best HR practices are as old as humanity itself in the African society and Zimbabwean culture in particular. This study explores concepts such as, team work, quality circles, total quality management, works councils, respect, harmony, collective bargaining, which have been part and parcel of the Zimbabwean culture since time immemorial and which are important as markers of HR practices.